SAFEGUARDING CHILDREN’S DATA IN THE DIGITAL AGE: A LEGAL APPROACH TO PREVENT CYBERATTACKS AND CHILD SEXUAL ABUSE - Gupta, Sumedha; Kumari, Sandhya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The growth of digital technologies and online platforms has dramatically increased the risk of children becoming victims of sexual abuse. Cybercriminals often abuse children's personal information, such as their name, age, location, and online activities, to identify and exploit them. However, this digital revolution has also led to increased risks, including the vulnerability of children's data to cybersecurity attacks. One of the most concerning consequences of such attacks is facilitating child sexual abuse. Therefore, protecting children's data is essential in preventing child sexual abuse. In this background based on this hypothesis, this paper focuses on the legal approach to protect the vulnerability of children's data from cybersecurity attacks. The paper analysis the legal frameworks and guidelines developed by the Indian government to safeguard the personal data of children. Further, it would identify the current gaps in the legal framework and emphasise the need for further improvements towards strengthening the data protection of children. Moreover, the paper explores the role of technology in protecting children's data, including data encryption, secure data storage, access controls, and monitoring systems and also analyses the challenges associated with implementing these technological solutions. Finally, the paper offers suggestions for policymakers, legal practitioners, and technology professionals to protect children's data from cyberattacks, thereby preventing child sexual abuse.